Shakespeare Rap (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
This work retells the famous balcony scene from Shakespeare’s Romeo and Juliet in the form of rap lyrics, merging Elizabethan literature with a contemporary mode of expression. I wrote and performed this work as part of my First-Year Writing Seminar about Shakespeare and music.For additional context, listen to the author's reflection on the piece below.